Utilization of Waste Tobacco (Nicotiana Tabacum) Post-Harvest as an Alternative Biodiesel - Donatus Setyawan Purwo Handoko (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aims of this research is process into biodiesel. Biodiesel is produced using transesterification reactions with variations of tempetature. Tobacco seed oil is extracted to obtain edible oils as biodiesel. The content of free fatty acid (FFA) in edible oils should be minimized to obtain a high yield of transesterification. The catalyst used in converting edible oils into biodiesel is homogeneous alkaline catalyst. Biodiesel with the higest yield from transesterification reactions with a temperature of 70 oC. Biodiesel was characterized the functional group and phsycal properties including density and viscosity